Experience of stigma and discrimination in families of persons with schizophrenia in the Czech Republic - Krupchanka, D; Chrtková, D; Vítková, M; Munzel, D; Čihařová, M; Růžičková, T; Winkler, P; Janoušková, M; Albanese, E; Sartorius, N (Social science & medicine (1982), 2018)
RATIONALE: Mental health-related stigma and discrimination not only affect persons living with schizophrenia but also their whole families. Stigma and discrimination reduction is key to respond to the unmet needs of persons with mental illness. The local context is of particular importance in this endeavor, as stigma and its manifestations depend on the specific conditions of the target population and across cultures and settings. Evidence on effective approaches to reduce stigma is sparse and lacking from Central and Eastern Europe, including from the Czech Republic. OBJECTIVE: Our aim was to inform an anti-stigma campaign undertaken in the framework of the national mental health reform in the Czech Republic. METHODS: We conducted a qualitative study based on semi-structured in-depth interviews with relatives of patients diagnosed with schizophrenia in the Czech Republic. Initial respondents were identified through local mental health services and users' organizations with a consecutive chain-referral sampling. Transcribed narratives were thematically analyzed within a pre-developed four-level thematic framework to comprehensively identify experiences of stigma and discrimination in all areas of the respondents' lives. RESULTS: Stigma experiences of 25 diverse family members of persons living with schizophrenia spanned four levels of respondents' lives (macro-, meso-, micro-, and intro-level). The overarching issues were: (1) general lack of understanding and misconceptions about mental illness; (2) structural discrimination and paucity of governmental and public support system; (3) burden of "pervasive and unlimited" care and inability of independent living. CONCLUSIONS: We identified several features of mental health related stigma and the ensuing discrimination in Czech Republic experienced by persons with severe mental illness and their relatives. We developed a set of recommendations for policy-makers aimed at reducing ignorance and prejudice amongst the public and professionals, improving health and social services-including employment, housing and community integration-and the provision of family support.
Keywords: Stigma; Central and Eastern Europe; Male; Family; rodina; služby péče o duševní zdraví; Schizophrenia; Česká republika; Adult; dospělí; mužské pohlaví; Health Care Reform; kvalitativní výzkum; Czech Republic; Family studies; lidé; ženské pohlaví; Mental Health Services; Humans; Mental health service; schizofrenie; reforma zdravotní péče; společenské stigma; Female; Qualitative Research; lidé středního věku; Social Stigma; Middle Aged